2021
DOI: 10.1111/ffe.13533
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analyses of damage behavior of wire with inclusion in multipass drawing process

Abstract: Inclusion is one of the main causes for unqualified wire. However, the forming mechanism of drawing fracture due to inclusions is still unclear. Therefore, it is significant to figure out the forming mechanism of wire drawing fracture with inclusions for designing and manufacturing high‐quality wires. In this paper, a physical model of wire with inclusion is established based on experimental observations. Multipass drawing is simulated by using finite element method (FEM) with the developed numerical damage mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…This was the rst evidence that a plastically manufactured component, apparently not awed, may contain some kind of discontinuity, thus a crack, inside. Recently Several studies on the phenomenon of central bursting and fracturing have been published, demonstrating that micro-voids form and develop during cold working and that central bursting and fracturing occur when voids reach a particular level [13][14][15][16]. Orbegozo [17] used an Instron testing machine to draw an aluminum wire in two passes in sequence from the initial state of 6.731 mm to 5.842 mm diameter, with a draw angle equal to 12 then the second pass from 5.842 mm to 5.461 mm the entry angle is 30 with a total reduction rate of 34%; using X-ray inspection to detect internal cuppy cracks.…”
Section: Introductionmentioning
confidence: 99%
“…This was the rst evidence that a plastically manufactured component, apparently not awed, may contain some kind of discontinuity, thus a crack, inside. Recently Several studies on the phenomenon of central bursting and fracturing have been published, demonstrating that micro-voids form and develop during cold working and that central bursting and fracturing occur when voids reach a particular level [13][14][15][16]. Orbegozo [17] used an Instron testing machine to draw an aluminum wire in two passes in sequence from the initial state of 6.731 mm to 5.842 mm diameter, with a draw angle equal to 12 then the second pass from 5.842 mm to 5.461 mm the entry angle is 30 with a total reduction rate of 34%; using X-ray inspection to detect internal cuppy cracks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wang et al 14 summarized the shapes of fracture caused by different types of inclusions in wire, and the results showed that pen‐tip shaped fracture is most obvious when the inclusion was close to the center of wire. Ma et al 15 analyzed the mechanism of pen‐tip shaped fracture of steel wire with central inclusion by finite element method, and the results indicated that this kind of fracture was mainly caused by the superposition of central and external V‐shaped damage. After multiple passes, the damage in the center of wire is the largest 16 .…”
Section: Introductionmentioning
confidence: 99%